Pengawasan DPRD dan Kendala-Kendala yang Dihadapi Terhadap Pengelolaan Keuangan Daerah - AD Basniwati (Fakultas Hukum Universitas Mataram, 2016)
Law No. 32 Year 2004 on Regional Government , gives broad authority to autonomous regions to organize Regional Government . With such authority , giving an opportunity for the region to explore and exploit all the potential that exists for the welfare of the people . In contrast with broad authority , also open opportunities for abuse of governmental authority , thus requiring supervision. With this research conducted , in hope will provide more advanced impact on the concept of financial management oversight by the Regional Chief and Council , so the possibilities are not in want will be solved as soon as possible . The method used in this study is a research method that uses normative law approach and conceptual approach , by conducting periodic review - review of the regulations in order to answer the law or which deals with issues that are relevant to the subject . Based on research conducted found : a. The shape of the Parliament supervision of financial management in achieving good local governance . b . Factors that constrain the supervision of Parliament for the area of financial management.